2002
DOI: 10.1038/sj.bjc.6600416
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of renal cell carcinoma angiogenesis and growth by antisense oligonucleotides targeting vascular endothelial growth factor

Abstract: Angiogenesis is critical for growth and metastatic spread of solid tumours. It is tightly controlled by specific regulatory factors. Vascular endothelial growth factor has been implicated as the key factor in tumour angiogenesis. In the present studies we evaluated the effects of blocking vascular endothelial growth factor production by antisense phosphorothioate oligodeoxynucleotides on the growth and angiogenic activity of a pre-clinical model of renal cell carcinoma (Caki-1). In vitro studies showed that tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…The in vitro experimental results in this study showed that VEGF antisense ODNs could decrease VEGF expression of cultured Walker-256 cells in a dose-dependent manner. Similar effect has been reported on other tumor cell lines [41,[44][45][46] . In in vivo study, we also found that VEGF antisense ODNs could inhibit VEGF expression of liver tumor tissues after TAE, reduce tumor MVD and growth rate in walker-256 cell transplanted rat liver cancer models.…”
Section: Discussionsupporting
confidence: 89%
“…The in vitro experimental results in this study showed that VEGF antisense ODNs could decrease VEGF expression of cultured Walker-256 cells in a dose-dependent manner. Similar effect has been reported on other tumor cell lines [41,[44][45][46] . In in vivo study, we also found that VEGF antisense ODNs could inhibit VEGF expression of liver tumor tissues after TAE, reduce tumor MVD and growth rate in walker-256 cell transplanted rat liver cancer models.…”
Section: Discussionsupporting
confidence: 89%
“…Elevated VEGF levels are associated with the progression of a variety of tumors and correlated to the outcome of cancer treatment (36,37). To date, numerous attempts to block the activity of VEGF have been made, including the use of antibodies (38), soluble VEGF receptors (39), VEGF receptor antagonists (40), or degradation of the VEGF message through the use of antisense oligonucleotides (41) or by RNA interference (42,43). The major focus of the previous studies was inhibition of a single target or a very limited number of targets.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of VEGF stimulates angiogenesis in human ovarian cancer xenografts (Duyndam et al 2002) and enhances tumorigenicity of U251 MG glioma cells in vivo (Ke et al 2002). Inhibition of tumor growth and angiogenesis in animal models has been demonstrated by neutralizing anti-VEGF antibody (Borgstrom et al 1998), reduction of VEGF expression by antisense cDNA (Im et al 1999;Luo et al 2001) or antisense oligonucleotides (Shi and Siemann 2002), soluble Flt-1 (Goldman et al 1998;Hoshida et al 2002), dominant negative Flk-1 (Millauer et al 1994), anti-KDR antibody (Sweeney et al 2002), Flk-1/KDR kinase inhibitor SU5416 (Fong TA et al 1999;Takamoto et al 2001), anti-VEGF 189 or anti-Flk-1 or Flt-1 ribozymes (Oshika et al 2000;Pavco et al 2000), and cytotoxic T-lymphocytes engineered to target Flk-1 (Niederman et al 2002). A synthetic peptide that blocks VEGF-KDR interaction or derives from the second Ig-like domain of Flt-1 can abolish angiogenesis in rabbit corneal and chick chorioallantoic membrane angiogenesis models, respectively (Binetruy-Tournaire et al 2000;Tan et al 2001).…”
Section: Vegf and Tumor Angiogenesismentioning
confidence: 99%